2012
DOI: 10.1002/eqe.2274
|View full text |Cite
|
Sign up to set email alerts
|

A procedure for generating performance spectra for structures equipped with passive supplemental dampers

Abstract: SUMMARY A procedure for estimating the peak response of SDOF systems equipped with passive supplemental dampers using code‐defined uniform hazard spectra is presented. The proposed procedure makes use of an improved equivalent linearization method that unifies the treatment of supplemental hysteretic and viscous‐viscoelastic damping and can be readily implemented in a computer script. Nonlinear time‐history analyses demonstrated that the proposed method makes significantly more reliable predictions than other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…For bilinear isolator models, Katsaras et al 15 found that this method overestimated the observed residual displacements in seismic isolators from previous earthquakes. 20 The same study noted that undamped free-oscillation tends to systematically underestimate the bilinear system residual displacement when viscous damping is present. This method was validated for bilinear systems using the residual ratio R s and subsequently extended to trilinear systems in Guo and Christopoulos.…”
Section: Predictors For Maximum Sample Residual Ratiomentioning
confidence: 93%
See 4 more Smart Citations
“…For bilinear isolator models, Katsaras et al 15 found that this method overestimated the observed residual displacements in seismic isolators from previous earthquakes. 20 The same study noted that undamped free-oscillation tends to systematically underestimate the bilinear system residual displacement when viscous damping is present. This method was validated for bilinear systems using the residual ratio R s and subsequently extended to trilinear systems in Guo and Christopoulos.…”
Section: Predictors For Maximum Sample Residual Ratiomentioning
confidence: 93%
“…The trilinear-plastic system is defined by 2 normalized yield displacements u 1 and u 2 , corresponding to 2 ductility parameters μ 1 = 1/u 1 and μ = 1/u 2 as shown in Figure 1B. 8,[18][19][20] In most practical applications, the quantity of interest is not R s , max , but rather the maximum residual ratio, R sp , max , that occurs in a random sample, which is affected by the post-peak response of the structure. The first post-yield branch has post-yield stiffness ratio p, while the second post-yield branch has zero stiffness.…”
Section: Residual Ratio Of Idealized Non-degrading Sdof Systemsmentioning
confidence: 99%
See 3 more Smart Citations